Strategi Madrasah Tsanawiyah dalam Meminimalisir Perilaku Indisipliner Siswa: Tsanawiyah Madrasah Strategy in Minimizing Student Indiscipline Behavior - Yanto, Yanto (STAI Publisistik Thawalib Jakarta, 2024)
The research aims to explain and describe the efforts of the school in minimizing student disciplinary behavior at Al-Mardliyyah Tagangser Laok Waru Pamekasan Islamic Junior High School. The research method used a qualitative approach with a case study design. Data collection was done through interviews, observations, and documentation. Data processing involved reduction, data presentation, and conclusion drawing. Data validity was ensured through credibility and confirmability. The research results show forms of disciplinary behavior such as arriving late to school, not participating in learning activities, leaving before time, not adhering to uniform regulations, bringing mobile phones to school, and being absent without explanation. The role of the class teacher includes being a parent figure, guidance counselor, motivator, administrator, and communicator. Discipline enforcement is carried out through a system of violation point weights which are socialized at the beginning of each new academic year packaged with the Student Introduction Period activities. A WhatsApp group facilitates communication between class teachers, guidance counselors, and the student affairs department. Collaboration between class teachers and guidance counselors involves formulating guidance procedures, compiling summaries, assigning home visit tasks, and monitoring and evaluation.